2017
DOI: 10.15448/2178-3640.2017.2.28633
|View full text |Cite
|
Sign up to set email alerts
|

Iranian EFL teachers' beliefs about how to Teach English Grammar

Abstract: The main purpose of this study is to investigate Iranian English teachers' beliefs about how to teach English grammar. For this purpose,forty-three teachers, eighteen females and twenty-five maleteachers from Kermanshah, Iran, participated in this study. To gather data in the studies about teacher beliefs, MacDonald Badger & White, (2001) questionnaire was used (TBQ). The questionnaire used for this study contained close-ended sections that required teachers to respond to statements on a five point Likert scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, the respondents in this study also describe positive responses from their students when grammar is being taught explicitly, such as their students' enthusiasm and the increasing test result of their students. To support the statement above, Janfeshan (2018) has asserted that teachers use approaches to grammar instructions according to their students ' expectations, meanwhile in Schulz (1996' expectations, meanwhile in Schulz ( , 2001 as cited in Janfeshan (2018), it is shown that language learners fiercely look forward to explicit grammar instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the respondents in this study also describe positive responses from their students when grammar is being taught explicitly, such as their students' enthusiasm and the increasing test result of their students. To support the statement above, Janfeshan (2018) has asserted that teachers use approaches to grammar instructions according to their students ' expectations, meanwhile in Schulz (1996' expectations, meanwhile in Schulz ( , 2001 as cited in Janfeshan (2018), it is shown that language learners fiercely look forward to explicit grammar instruction.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Niu and Andrew (2012) in Rahman & Rashid (2017), it is important to conduct a study towards teacher's beliefs for teacher beliefs are vital components that can give strong effect in teaching practice since it is defined as "teachers' thoughts about what should be done with teaching." Clark and Peterson (1986), in Janfeshan (2018) also pointed out that teachers' beliefs were generally considered a main determinant of instructional activity and of student learning, thus it was important to explore about teachers' belief because it would reflect everything they do in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also studies that report the dominance of the teacher. For example, Janfeshan (2017) and Mardali et al (2019) reported that Iranian EFL emphasized teachers' role in the instruction process rather than students, which the authors attributed to the exam-based culture and traditional teaching in Iran.…”
Section: Discussionmentioning
confidence: 99%